SIMBOL KEKUATAN ADAT-ISTIADAT BALI DALAM NOVEL INCEST KARYA I WAYAN A - Desyarini Puspita Dewi (LPPM Universitas Pekalongan, 2016)
This study aimed to describe (1) the form of a symbol of strength in the novel Bali customs Incest, and (2) the function symbol of strength customs Bali for citizens owner contained in the novel Incest. Source of research data is a novel Incest (2008) by I Wayan Artika issued by the issuer Pinus Yogyakarta and research instruments are human instrument. Data collected by reading and recording techniques, while data analysis was done by using descriptive qualitative measures-inductive comparative categorization, tabulation, and inference. Validity of the data obtained through the semantic validity and consultation of experts (expert judment validity) and reliability intereter. The results showed that the form of the symbol of the power of the customs of Bali consists of (1) Symbol of Strength Customs Bali in the realization of the Ideal of Culture, includes (a) myth (myth twin buncing and myths of incest), (b) trust, and (c) customary law ; (2)Symbol of Strength Customs Bali in Physical Form, include (a) the temple, (b) the village hall or bale train, (c) langking langkau, and (d) kulkul; and (3) Symbol Power of Customs Bali in FormSocial Activities, includes (a) traditional organizations (Wipe Truna-Truni, Subak, and Tempekan), (b) the ceremony, (c) indigenous stakeholders, (d) mutual assistance, (e) consultation, (f) art, and (g) idle. Function symbol of strength customs for the public wearer contained in the novel Incest, include: reinforces the view of life citizens, as a medium of communication between man and God / Hyang Widhi, between man and his neighbor or other beings, and between human and the natural environment, and as a unifying kinship between the various groups. In general, the three form a symbol of the power of the customs of Bali above has the function reinforces the view of life of the community. For the third second function is filled by a form of traditional power symbol istidat be physical and social activity.